2017
DOI: 10.3390/cancers9070079
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Integrin α6β4 Glycosylation in Cancer

Abstract: Malignant transformation is accompanied with aberrant glycosylation of proteins. Such changes in glycan structure also occur in the integrins, which are a large family of cell surface receptors for the extracellular matrix and play key roles in tumor progression. There is now increasing evidence that glycosylation of integrins affects cellular signaling and interaction with the extracellular matrix, receptor tyrosine kinases, and galectins, thereby regulating cell adhesion, motility, growth, and survival. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…Surprisingly, exosomederived ENO1 can also upregulate integrin α6β4 expression in recipient cells, which exhibit increased proliferative activity, migratory and invasive capacities, and EMT activation. Integrin α6β4 is a crucial protein complex involved in the spreading and metastasis of tumor cells 65,66 . Integrin α6β4 separates from hemidesmosome-like structures in tumors, and this separation not only causes tumor cells to lose polarity and detach from the basement membrane but also causes upregulation of free integrin α6β4, which functions in bidirectional signal transduction and can, in turn, activate the relevant signaling pathways to promote tumor growth and metastasis 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, exosomederived ENO1 can also upregulate integrin α6β4 expression in recipient cells, which exhibit increased proliferative activity, migratory and invasive capacities, and EMT activation. Integrin α6β4 is a crucial protein complex involved in the spreading and metastasis of tumor cells 65,66 . Integrin α6β4 separates from hemidesmosome-like structures in tumors, and this separation not only causes tumor cells to lose polarity and detach from the basement membrane but also causes upregulation of free integrin α6β4, which functions in bidirectional signal transduction and can, in turn, activate the relevant signaling pathways to promote tumor growth and metastasis 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in Golgi organization and function might contribute to how proteins and lipids are processed and delivered ( Bankaitis et al, 2012 ; Rodriguez-Boulan and Müsch, 2005 ), which could also affect anchorage-dependent signaling. Malignant transformation in cancer cells is accompanied by aberrant glycosylation of proteins, including integrins and cadherins ( Kariya et al, 2017 ; Varki et al, 2009 ). In many cancers, the Golgi is fragmented to drive this change ( Migita and Inoue, 2012 ; Petrosyan, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated and suprabasal expression of integrin α6β4 is seen in all stages of squamous cell carcinoma (SCC) progression and it has been reported that high suprabasal expression primes SCCs for early relapse [68,[70][71][72]. Multiple mechanisms and molecular pathways, including glycan modifications and modulation of the immune microenvironment, underlie integrin α6β4-mediated tumor progression and are extensively reviewed elsewhere [73].…”
Section: Integrin α6β4mentioning
confidence: 99%